Development and psychometric verification of body existence diagnostics (BED) - Maksim YU. Lutsik; Anna V. Drongo (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Existential givenness is the main categories with which work takes place in existential analysis for the actualization of client being. Despite this, they have little operationalization and are poorly accessible to quantitative measurement methods. They are often investigated only through phenomenological means, which limits the possibilities of working with them. Especially it concerns the measurement of physicality, which has recently been discarded in favor of ontocentric spheres. Because of this, it is not always possible to understand the phenomenology of the inner world fairly accurately and in an accessible way, because the main existential, expressed in the possibility of being physically in this world, is not taken into account. It is also impossible to standardize the method of work and explore its effectiveness of psychotherapy without special tools. On the basis of this, the diagnosis of existential corporeality was developed. It investigated as a multidimensional phenomenon of the client's experience of its physical manifestation in the world. Specific methodological foundations were identified for creating diagnostics. The structure of the methodology and stimulus material was developed, which for the most part confirmed in factor analysis, only the Umwelt sphere - the objective world does not fully correspond to the expected characteristics. Convergent validity was established, which confirmed the subject of this tool, and also revealed the structure of bodily existential, which affects all other ontological characteristics. It confirms the hypothesis of necessary physicality basis for being. All major psychometric parameters were established, DET has high rates of convergent, prognostic and structural validity and reliability. This diagnosis can be used in practical work of a psychologist in the role of screening diagnosis, or the same as the reference stimulus material to be discussed at the session and allowing client to directly face the existential sphere of being.